Ecology and management of neotropical migratory birds : a synthesis and review of critical issues - Finch, Deborah M.; Martin, Thomas E. (Thomas Edward), 1953- (Oxford University Press, 1995)
Introduction, Martin & Finch. 1. Population Trends and the North American Breeding Bird Survey, by Peterjohn, Sauer, & Robbins. 2. The Strength of Inferences About Causes of Trends in Populations, by James & Charles E. McCulloch. 3. When and How are Populations Limited, by Rotenberry, Cooper, Wenderle & Smith. 4. Summer vs. Winter Limitation of Populations, by Sherry & Holmes. 5. Habitat Requirements During Migration, by Moore et al. 6. Habitat Use and Conservation During Winter in the Neotropics, by Petit et al. 7. Impacts of Silviculture, by Thompson, Probst & Raphael. 8. Effects of Silvicul.